The Role of Job Satisfaction as a Mediation of the Influence of Individual Characteristics and Organizational Culture on the Performance - Ortalita, Maulidya; Setyanti, Sri Wahyu Lelly Hana; Sudarsih, Sudarsih (PT FORMOSA CENDEKIA GLOBAL, 2025)
Human resources are one of the assets of an agency that will determine the success or failure of the agency, because human resources are the most important factor in carrying out and achieving agency goals. This research aims to determine and analyze the role of job satisfaction as a mediating influence of individual characteristics and organizational culture on employee performance. The object of this research is the Jember Regency Transportation Service, with a permanent employee population of 54 people and the sample in this research is 54 respondents. In this study, the total number of variable indicators is 17. The data analysis method used in this research is path analysis. The results of this research indicate that individual characteristics and organizational culture have a significant effect on the performance of permanent employees at the Jember Regency Transportation Service.